Effect of added fat on the plasma glucose and insulin response to ingested potato given in various combinations as two meals in normal individuals - (:unkn) unknown (American Diabetes Association Inc., 1994)
OBJECTIVE - In normal subjects, ingestion of fat with potato in a morning meal resulted in a decrease in the glucose response. Therefore, we wished to determine whether a fat-induced decrease in blood glucose also would be observed after a second identical meal. In addition, we were interested in determining if fat ingestion with a morning meal would have an effect on the blood glucose and insulin responses to a second meal not containing fat. RESEARCH DESIGN AND METHODS - Nine healthy male subjects ingested two meals consisting of an amount of potato containing 50 g carbohydrate, either alone or with 50 g fat as butter. The meals were served in four combinations as follows: 1) potato for the first meal, potato for the second meal; 2) potato for the first meal, potato with fat for the second meal; 3) potato with fat for the first meal, potato for the second meal; and 4) potato with fat for the first meal, potato with fat for the second meal. Meals were ingested at 8:00 A.M. and noon. Plasma glucose and C-peptide, serum insulin, triglyceride, and free fatty acid (FFA) concentrations were determined over an 8-h period. The integrated area responses to the meals were quantified over the subsequent 4-h period using the fasting value or the noon value as baseline for the first and second meals, respectively. RESULTS - When the first meal contained potato only, the glucose area response to the second meal was significantly less when the second meal contained fat. However, fat ingestion had no effect on the glucose area response to the second meal when fat was present in the first meal. The insulin area responses to the first and second meals were similar after ingestion of potato or potato with fat. However, the insulin response to the second meal always was less than that to the first meal. The C-peptide area responses after ingestion of the second meal also were all higher than those after the first meal. The triglyceride area responses were slightly negative after ingestion of potato alone in the first meal. When fat was ingested, they were positive. When the first meal contained fat but the second meal did not, there was a rise in triglyceride concentration after the second meal as well as after the first meal. That is, a rise occurred without ingestion of fat with the second meal. If fat was present in the second meal the rise was even greater. The FFA area responses were similar to the triglyceride area responses. CONCLUSIONS - When fat was ingested with carbohydrate in either the first or second meal, the glucose area response was decreased. However, when both meals contained fat, a decrease in the glucose area response did not occur with the second meal. The glucose area responses all were greater after the second meal compared with those after the first meal, i.e., the opposite of a Staub-Traugott effect was observed. The insulin area responses to the first and second meals were similar whether fat was ingested or not.